Corporate Bond Valuation and Hedging with Stochastic Interest Rates and Endogenous Bankruptcy - Acharya, Viral V.; Carpenter, Jennifer N. (Review of Financial Studies, 2002)
This paper analyzes corporate bond valuation and optimal call and default rules when interest rates and firm value are stochastic. It then uses the results to explain the dynamics of hedging. Bankruptcy rules are important determinants of corporate bond sensitivity to interest rates and firm value. Although endogenous and exogenous bankruptcy models can be calibrated to produce the same prices, they can have very different hedging implications. We show that empirical results on the relation between corporate spreads and Treasury rates provide evidence on duration, and we find that the endogenous model explains the empirical patterns better than do typical exogenous models.